Teachers' Efforts to Improve Discipline Through Sociodrama for Class IV Mildly Mentally Impaired Children at SLB YPDP and SLB Bina Kasih Bandung - Zakia, Helmi; Khoerani, Riska; Suwandari, Lilis (Angstrom Centre of Education, 2024)
A mentally retarded child is a child with special needs who has an abnormality in terms of an intelligence level below average. The condition of mentally retarded children who have intellectual and adaptive obstacles and are unable to think abstractly hinders learning activities. Teachers need methods that can be used to provide learning for children, one of the learning methods that can be done is through sociodrama. The research was conducted in two schools using descriptive qualitative research methods, observation, interview and documentation data collection techniques. The research subjects were teachers and children with mild intellectual disabilities. The results of the research show that children with mild mental retardation are able to carry out the discipline that has been taught at school and apply it to everyday life, but in certain aspects mentally retarded children still need guidance and assistance from teachers. Recommendations are aimed at teachers and schools which teachers should provide guidance and developing potential in children, by using appropriate learning strategies, teaching methods and media, so as to provide motivation to both children and all class teachers to develop learning programs.